Kafaah as a Tool of Social Legitimacy in Marriage: An Empirical Analysis of Maslahah and Discrimination in Banda Aceh City - Solin, Siti Dian Natasya; Zubaidi, Zaiyad; Abdul Muthalib, Salman; Abdussalam, Izuddin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study examines kafa'ah as a tool of social legitimacy in marriage by examining the tension between the goal of maintaining maslahah (maintaining benefits) and the potential for discrimination that arises in the practices of the people of Banda Aceh City. Historically, kafa'ah was formulated in classical Islamic jurisprudence to maintain family harmony, but in the modern context, this concept often shifts into a social selection mechanism that gives rise to rejection of marriages based on lineage, economics, education, or social status, including in certain communities such as sayyid-syarifah and families with high dowry demands. To examine this phenomenon, this study uses a socio-legal approach by combining a review of Islamic jurisprudence literature, an analysis of Islamic family law regulations, and empirical data from interviews with victims of discrimination, religious leaders, and academics. The findings indicate that the expansion of kafa'ah criteria beyond religious and moral aspects is more influenced by socio-historical constructions than normative sharia considerations, so that its practice often reinforces social hierarchies and creates exclusion of certain individuals or groups. This study concludes that kafa'ah needs to be reconstructed as a flexible social consideration and should not be used as a basis for limiting the right to marry, so that it remains in line with the principles of maslahah, justice, and the goals of Islamic family law in realizing a harmonious family.